Predictive factors of falls in women practicing physical exercise - Nascimento, Marcelo de Maio (2017)
Objective: To identify factors associated with the risk of falls in older women engaged in regular physical exercise. Methods: Observational cross-sectional study with a non-probability and intentional sample conducted between April and July 2016 in Petrolina, Pernambuco, with 109 women (60-84 years old) doing Pilates, water aerobics and swimming, with and without history of falls. A questionnaire addressing sociodemographic data, comorbidities and number of medications used was used as the instrument of data collection in addition to Body Mass Index (BMI), gait performance by the Time Up and Go (TUG) test and balance by the Berg Balance Scale (BBS). Data were analyzed using Kruskal Wallis test, Spearman’s correlation and linear regression. Results: A gait performance deficit was observed with advancing age (p